Many foliar endophytic fungi of Quercus gambelii are capable of psychrotolerant saprotrophic growth. - Emily Weatherhead; Emily Lorine Davis; Roger T Koide (PLoS ONE, 2022)
Many endophytic fungi have the potential to function as saprotrophs when living host tissues senesce and enter the litter pool. The consumption of plant litter by fungi obviously requires moisture but, in the arid, western USA, the native range of Quercus gambelii Nutt., most of the precipitation occurs during the coldest months of the year. Therefore, we hypothesized that the endophytic fungi of Q. gambelii have the potential to function as psychrotolerant saprotrophs, which we defined in this study as an organism capable of significant growth on leaf litter at 5°C. We further hypothesized that a tradeoff exists between growth of endophytic fungi at 5°C and at 17°C such that fungal isolates are either cold- or warm-temperature specialists. Consistent with our first hypothesis, we found that 36 of our 40 isolates consumed leaf litter at 5°C, but there was a surprisingly high degree of variability among isolates in this ability, even among isolates of a given species. Contrary to our second hypothesis, there was no tradeoff between saprotrophic growth at 5°C and saprotrophic growth at 17°C. Indeed, the isolates that grew poorly as saprotrophs at 5°C were generally those that grew poorly as saprotrophs at 17°C. By virtue of being endophytic, endophytic fungi have priority in litter over decomposer fungi that colonize plant tissues only after they enter the litter pool. Moreover, by virtue of being psychrotolerant, some endophytic fungi may function as saprotrophs during the cold months of the year when moisture is temporarily available. Therefore, we suggest that some endophytic fungi of Q. gambelii could play significant ecosystem roles in litter decomposition and nutrient cycling.